Problem-Solving Using Logic and Reasoning, Mathematics, Algorithms, Python and Generative AI - Gao, Weizheng; Allagan, Julian D.; Gao, Shanzhen; Su, Jianning; Malomo, Olumide; Eyob, Ephrem; Adekoya, Adeyemi (Proceedings (International Conference on Computational Science and Computational Intelligence), 2023)
Problem-solving is essential in various fields, including business, technology, and everyday life. It often involves a combination of experience, knowledge, intuition, and rational analysis. Furthermore, it requires integrating disciplines such as logic and reasoning, mathematics, algorithms, Python, and generative AI in today's complex world. We will provide detailed descriptions of how to solve problems based on integrating previously mentioned disciplines. Later, we will discuss how to guide students through making intelligent investment decisions.